PROFILE OF ENDOMETRIOSIS PATIENT IN Dr. SAIFUL ANWAR HOSPITAL MALANG- EAST JAVA 2001 – 2003 - Kusuma Andriana, I Wayan Arsana W (Jurnal Gamma, 2006)
The general aim of the study wants to know the profile of endometriosis patient in dr. Saiful Anwar hospital Malang - East Java for 3 years (2001-2003). The special aim wants to know the epidemiology, clinical symptoms, how to make the diagnosis, therapy and post therapy evaluation. The population are out patient care medical record in gynecology department of dr. Saiful Anwar hospital Malang-East java. The samples are all of the out patient care medical record in gynecology department from January 2001 - December 2003, and definitely diagnosis from anatomy pathologic examination. 34 samples were included in this study; the mean age was 34.4 year, and infertile samples were 35.29 %. The most symptoms was menstrual pain (70.59%) with 52.94 % pain during the menstruation and 29.38 % before it. In the first time 88.26 % cases were not diagnosed as endometriosis, but encounter in laparatomy and or anatomy pathologic examination. From anatomy pathologic examination, the most location was ovarium (67.65 %). The most therapy was DMPA injection (82.36 %) and 91.18 % samples not performed post therapy evaluation.